PENGARUH PEMBERIAN TEH DAUN SIRSAK TERHADAP PENURUNAN NILAI MAP (MEAN ARTERIAL PRESSURE) PADA LANSIA PENDERITA HIPERTENSI - Sari, Gevi Melliya; Prawito; Puspita, Enny; Agustin, Elsa; Rustanti, Elly (PRIMA WIYATA HEALTH, 2025)
Background: Mean arterial pressure (MAP) in the context of hypertension was important in understanding the impact of high blood pressure on the elderly. Several pharmacological and non-pharmacological therapies are expected to help reduce MAP values ​​in the elderly with hypertension. Soursop leaf tea, rich in antioxidants and potassium, is one of the non-pharmacological therapies that can lower blood pressure in people with hypertension. Objectives: The purpose of this study was to determine the effect of giving soursop leaf tea on reducing MAP (Mean Arterial Pressure) values ​​in elderly people with hypertension in Simongagrok Village, Dawarblandong District, Mojokerto Regency. Methods: This study used a Pre-Experiment design using the (One-Group Pretest-Posttest) approach. In this study, a population of 19 elderly people in Simongagrok Village was obtained with a sample size of 15 respondents using the Quota Sampling technique. The instruments in this study were a blood pressure meter, observation sheets, and soursop leaf tea. Data analysis used the Wilcoxon Sign Rank Test. Results: The results of the study before being given treatment showed that 13 respondents (86.7%) experienced hypertension in the category of Mild MAP Value. After being given treatment, 15 respondents experienced hypertension in the category of Normal MAP Value with a percentage of 100%. Based on the results of the Wilcoxon test, a significant value was obtained, namely p ≤ ???? 0.05, namely 0.001 <0.05, which means that ????1 is accepted, so there is an effect of giving soursop leaf tea on reducing MAP (Mean Arterial Pressure) values ​​in elderly people with hypertension in Simongagrok Village, Dawarblandong District, Mojokerto Regency. Conclusion: Giving soursop leaf tea is expected to be one of the independent therapies for nurses in providing non-pharmacological therapy in reducing MAP values ​​in elderly people with hypertension.